(3QSGdI aj GdYed HGdQHY GdeLjHs - (3GdOeTbqj GdeGpQOjfj, SHW GdeGQOjfj, HOQ GdOjf (B- (3GdZRGd, eMeO Hf eMeO Hf CMeO, (B912 (3g`s
(3ChdgG (B:s
(3GdMeO ddg agPg QSGdI aj GdYed HGdQHY GdeLjH eTJedI Ydi ebOeI hYTQjf HGHG aGdebOeI aj JSejI QSheg aChdgG GdeQcR hgh GdMQe GdPj ajg GdNjW hjSei GdbWH bhS GdGQJaGY s
(3BNQgG (B:s
(3GdHGH GdYTQhf aj GdYed HGdchGcH ; Cbe HYO GdchGcH ebGe ejd GdTeS hGSJNQL efg SYI eTQbI hZGjI hcPG GQJaGY GdPj dG SeJ dg Ef cGf HYOg TeGdjG JeJs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ dcJGH GdeDda faSg GdeSei (B: (3GdeWdH, aj GdYed HGdQHY GdeLjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\54s
(3cTa GdXfhf (B2\1109s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs